An improved approach for water quality evaluation: TOPSIS-based informative weighting and ranking (TIWR) approach. (June 2018) - Li, Zhenya; Yang, Tao; Huang, Ching-Sheng; Xu, Chong-Yu; Shao, Quanxi; Shi, Pengfei; Wang, Xiaoyan; Cui, Tong
Highlights: An improved TOPSIS-based approach called the TIWR approach is proposed. It considers the effect of correlation among indicators using CRITIC approach. An appropriate method for coupling indicators and associated standards is presented. A delicate level of water quality makes objects/monitoring sites distinguishable. It can avoid some unreasonable results obtained by traditional approach. Abstract: A great deal of effort has been made on the development of approaches based on Technique for Order Preference by Similarity to Ideal Solution (TOPSIS). Little attention is, however, paid to how to couple water quality indicators and their officially-defined standards with consideration of inter-correlation among indicators when TOPSIS is applied for evaluating water quality. This study proposes an improved TOPSIS-based approach called the Informative Weighting and Ranking (TIWR) approach. It couples water quality indicators and associated standards over the entire process and considers inter-correlation among indicators using the Criteria Importance Through Inter-criteria Correlation (CRITIC) approach. The approach is applied to the water quality evaluations of the Shitoumenkou reservoir and the Lake Tai. Results suggest that it produces a delicate level Hi associated with water quality for an object/monitoring site, which avoids classifying several objects into the same typical level and makes them distinguishable. The TIWR approach agrees well with traditional approach when a level Hi is transformed to a typical level. In addition, it can avoid some unreasonable results obtained by traditional approach. These findings have implications for decision makers and researchers in applying the TIWR approach in water environment protection and management.